Nilai-nilai Moral pada Cerpen Pelajaran Mengarang Karya Seno Gumira Ajidarma serta Implikasi terhadap Pembelajaran Bahasa Indonesia di SMP - Aripin, Enjen Zaenal; Asuti, Tri; Suhardjono, Dadi Waras (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
In this thesis the author discusses the Moral Values in Short Stories Composing Lessons by Seno Gumira Ajidarma and the Implications for Language Learning in Indonesian Middle Schools. This research aims to describe the form of conveying moral values in the short story "Writing Lessons" by Seno Gumira Ajidarma. The type of research used is qualitative descriptive research with content analysis methods (literature study). The focus of the research is on the form of moral values contained in the short story "Lesson of Writing" by Seno Gumira Ajidarma. The technique used in this research uses note-reading techniques, in the form of words, sentences and paragraphs. The results of the research obtained 3 forms of moral values in the short story "Lesson of Writing" by Seno Gumira Ajidarma, namely, there are 6 data on the human relationship with oneself, 4 data on the human relationship with other people and 2 data on the human relationship with God. The results of this research can be applied to contribute to Indonesian language learning regarding moral values in short stories.